1999
DOI: 10.1104/pp.120.2.361
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity of Barley Aleurone Tissue to Gibberellin Is Heterogeneous and May Be Spatially Determined1

Abstract: In cereals, gibberellin (GA) enhances the synthesis and secretion of hydrolytic enzymes from aleurone cells. These enzymes then mobilize the endosperm storage reserves that fuel germination. The dose-response curve of aleurone protoplasts to GA extends over a range of concentrations from 10 ؊11 to more than 10 ؊6 M. One hypothesis is that subpopulations of cells have different sensitivities to GA, with each cell having a threshold concentration of GA above which it is switched on. The dose-response curve there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…Even though the entire seed is in contact with the imbibition solution containing GA, LeEXP4 mRNA is detected only in the endosperm cap (Bradford et al, 2000), indicating that its promoter is sensitive to regulation by both cell type and GA. It is also possible that the sensitivity of cells to GA is greater in the micropylar (proximal) part of the seed as has been shown for barley aleurone layer cells (Ritchie et al, 1999).…”
Section: Discussionmentioning
confidence: 96%
“…Even though the entire seed is in contact with the imbibition solution containing GA, LeEXP4 mRNA is detected only in the endosperm cap (Bradford et al, 2000), indicating that its promoter is sensitive to regulation by both cell type and GA. It is also possible that the sensitivity of cells to GA is greater in the micropylar (proximal) part of the seed as has been shown for barley aleurone layer cells (Ritchie et al, 1999).…”
Section: Discussionmentioning
confidence: 96%
“…Changes in PSVs have been reported in the aleurone or endosperm of cereals , dicots (Nonogaki et al, 1998), and in proteinstoring cotyledons (Gifford et al, 1983). In cereal aleurone cells, vacuolation has been shown to be a reliable assay for the response of this tissue to GA (Bush et al, 1986;Bethke et al, 1998;Ritchie et al, 1999). There is general agreement that vacuolar storage proteins are proteolyzed and that the resulting amino acids and peptides are used for de novo protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…This process of vacuolation has been used as a semiquantitative marker for GA-dependent events (Bush et al, 1986;Ritchie et al, 1999). We quantified the number of vacuoles per aleurone cell at various times after imbibition of Arabidopsis seeds to determine if a similar vacuolation process occurs in the Arabidopsis aleurone cell.…”
Section: Arabidopsis Aleurone Cells Undergo Characteristic Changes Inmentioning
confidence: 99%
“…Kar-Roy et al showed that an enhanced GFP (EGFP) was a more sensitive reporter than chloramphenicol acetyl transferase (CAT) in HeLa cells at low DNA concentrations, while CAT became more dominant at higher DNA doses, which they explained by possible enzymatic amplification of the signal (48). Alternatively, stable transformation of GFP-expressing inducible cassettes could enhance the signal-to-noise ratio and allow, for example, further analysis of the heterogeneous nature of plant hormone sensitivity (39).…”
Section: Discussionmentioning
confidence: 99%
“…We interpret our results to indicate that the subpopulation of transformed cells responds uniformly to ABA signaling effectors. The homogeneous nature of the rice protoplast response to ABA revealed by FCM is in contrast to gibberellin response in barley protoplasts (39), and stands as an example of the value of FCM over traditional biochemical methods. By utilizing the non-ABA-inducible Ubi-GFP construct, we directly demonstrated the specificity and magnitude of ABA induction of gene expression (Fig.…”
Section: Discussionmentioning
confidence: 99%